2013
DOI: 10.3390/ijms14059883
|View full text |Cite
|
Sign up to set email alerts
|

Rab27 GTPases Distribute Extracellular Nanomaps for Invasive Growth and Metastasis: Implications for Prognosis and Treatment

Abstract: The Rab27 family of small GTPases regulates exocytosis of distinct vesicle types including multivesicular endosomes, which results in the release of exosomes. Exosomes are nanometer-sized membrane vesicles that enclose soluble factors such as proteins and nucleic acids within a lipid bilayer and can travel toward distant tissues to influence multiple aspects of cell behavior. In our view that tumors are endocrine organs producing exosomes, Rab27 GTPases and their effector proteins are critical determinants for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Rab27a and Rab27b, as well as their effector proteins, are important regulators of exosome release [77,163]. Interestingly, silencing Rab27a by RNA interference disrupted exosome-dependent and -independent mechanisms that modify the tumor microenvironment and can also reduce tumor growth and metastasis [164].…”
Section: Exosome-based Diagnostics and Therapeuticsmentioning
confidence: 99%
“…Rab27a and Rab27b, as well as their effector proteins, are important regulators of exosome release [77,163]. Interestingly, silencing Rab27a by RNA interference disrupted exosome-dependent and -independent mechanisms that modify the tumor microenvironment and can also reduce tumor growth and metastasis [164].…”
Section: Exosome-based Diagnostics and Therapeuticsmentioning
confidence: 99%
“…The Rab27 family of small GTPases, as well as their effector proteins synaptotagmin-like protein 4 (Slp4) and synaptotagmin-like protein homologue lacking C2 domains b (Slac2b), have been found to be important regulators of exosome release [57, 58]. Alternatively, formation of microvesicles via direct shedding from the cancer cell surface may be controlled by specific signalling pathways triggered by Ras homolog family member A (RhoA) [59] and/or ADP-ribosylation factor 6 (Arf6) [60].…”
Section: Extracellular Vesicles: Emerging Targets For Cancer Therapymentioning
confidence: 99%
“…However, technological challenges related to EV isolation, purification and content analysis remain. For example, for multicentre validation studies, standardized isolation and characterization methods are necessary, yet largely lacking [58]. To overcome some of these challenges, a novel platform has recently been described for rapid protein profiling of EV samples.…”
Section: Figurementioning
confidence: 99%
“…The study demonstrated that the presence of Rab27 was significantly correlated with reduced overall survival. 137 Mutlivariate analyses also implicated Rab3c as a prognostic marker in both early and later stage colon cancer patients, as high Rab3c expression influenced cancer stage and subsequent therapy. 138 This opens the doors to the development of new therapeutic methods to target these necessary proteins such as siRNA or peptide manipulations that can selectively affect Rab effectors.…”
Section: Resultsmentioning
confidence: 99%